Emergence of orbital two-channel Kondo effect in epitaxial TiN thin films. (January 2022) - Gupta, Siddharth; Sachan, Ritesh; Narayan, Jagdish
Abstract: The continual scaledown and stringent defect control in electronic devices are opening up frontiers in Kondo effect-a powerful testbed for probing magnetic impurity coupling to a continuum of electronic states. In disordered ferromagnets, degenerate quantum states like two-level systems (TLS) with a pseudo-half spin can couple with the continuum to mimic Kondo physics, creating the orbital two-channel Kondo (2CK) effect below the characteristic Kondo temperature ( T K ). By employing vacuum-annealing to inject ∼12 at.% nitrogen vacancies (VN ) in TiN1-x films, we generated room-temperature ferromagnetic ordering with 13.6 emu g −1 saturation magnetization. The transport characteristics exhibited non-Fermi-liquid (NFL) behavior below T K of 20.2 K. The orbital 2CK effect is signified by a clear transition from logarithmic ( T < T 0 ∼40 K), to square-root dependence ( T < T K ) and subsequent deviation from it ( T < T D ∼10 K) in resistivity upturn behavior in three distinct low-temperature regimes. By controlling VN, we establish the necessity of ferromagnetism and ultrafast tunneling centers for generating orbital 2CK effect and NFL behavior in disordered metallic systems, extending their scope in non-magnetic nanomaterials. Highlights: Vacuum annealing in TiN1-x films results in non-Fermi-liquid behavior below the characteristic Kondo temperature ( T K ) of 20.2 K. TiN1-x films exhibit VN (∼12 at.%), with minimal O incorporation due to the highly non-equilibrium nature of pulsed laser deposition. Ti +2 polarons are magnetically active defects that can be tuned to generate the orbital 2CK effect with non-Fermi liquid behavior and ferromagnetic ordering. N atoms tunnel across the periodic dislocations at the TiN/Al2 O3 heteroepitaxial interface created during domain matching.